Hubungan riwayat jatuh, jenis kelamin, dan status gizi dengan TUGT pada lansia - Gultom, Miranda; Balyas , Abi Bakring; Widodo, Sutopo Marsudi; Kahanjak, Donna Novina; Augustina, Indria (Barigas: Jurnal Riset Mahasiswa, 2024)
The occurrence of falls among the elderly is a result of the aging process, which can lead to injuries and physical limitations. A history of falls, gender, and nutritional status are estimated to influence the risk of falling. To evaluate the relationship between a history of falls, gender, and nutritional status and the results of the TUGT using a descriptive analytical design with a cross-sectional approach, the study sample consisted of 30 elderly people. Data analysis was performed using SPSS software, applying Fisher’s Exact Test and Spearman correlation tests. There is a relationship between a history of falls and nutritional status and the results of the TUGT in the elderly with p-value = 0,000. However, no significant relationship was found between gender and the results of the TUGT. This study provides evidence that a history of falls and nutritional status influence balance in the elderly.